Genotypic differences in intruder-evoked immediate early gene activation in male, but not female, vasopressin 1b receptor knockout mice. Issue 1 (December 2016) - Witchey, Shannah; Stevenson, Erica; Caldwell, Heather
Abstract Background The neuropeptide arginine vasopressin (Avp) modulates social behaviors via its two centrally expressed receptors, the Avp 1a receptor and the Avp 1b receptor (Avpr1b). Recent work suggests that, at least in mice, Avp signaling through Avpr1b within the CA2 region of the hippocampus is critical for normal aggressive behaviors and social recognition memory. However, this brain area is just one part of a larger neural circuit that is likely to be impacted in Avpr1b knockout (−/−) mice. To identify other brain areas that are affected by altered Avpr1b signaling, genotypic differences in immediate early gene activation, i.e. c-FOS and early growth response factor 1 (EGR-1), were quantified using immunocytochemistry following a single exposure to an intruder. Results In females, no genotypic differences in intruder-evoked c-FOS or EGR-1 immunoreactivity were observed in any of the brain areas measured. In males, while there were no intruder-evoked genotypic differences in c-FOS immunoreactivity, genotypic differences were observed in EGR-1 immunoreactivity within the ventral bed nucleus of the stria terminalis and the anterior hypothalamus; with Avpr1b −/− males having less EGR-1 immunoreactivity in these regions than controls. Conclusions These data are the first to identify specific brain areas that may be a part of a neural circuit that includes Avpr1b-expressing cells in the CA2 region of the hippocampus. It is thought that this circuit, when working properly, plays a role in how an animal evaluates its social context.